Hospital malnutrition in chronic kidney disease: a retrospective cohort study from eastern Indonesia. - Kotha, Pingkan; Rasyid, Haerani; Daud, Nurpudji A.; As'ad, Suryani; Bukhari, Agussalim; Syauki, Yasmin (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: Malnutrition in hospitalized patients, particularly those with chronic kidney disease (CKD), significantly impacts morbidity and mortality. This study addresses the prevalence and factors contributing to malnutrition in CKD patients at Dr. Wahidin Sudirohusodo Hospital (RSWS) Makassar, Indonesia. Objective: This study aimed to examine the prevalence of malnutrition and its associated risk factors among hospitalized CKD patients from January 2022 to January 2024. Methods: A retrospective cohort design was employed, including CKD patients aged over 18 who were hospitalized for at least 14 days. Nutritional status was assessed using the Malnutrition Screening Tool (MST) modified Dr. Wahidin Sudirohusodo Hospital (RSWS), Makassar. Data were collected from medical records and analyzed using univariate and bivariate statistical methods. Results: We found that 42% of CKD patients were at moderate to severe risk of malnutrition using the modified MST. Significant correlations were found between MST scores and inflammatory markers, particularly albumin (p = 0.039) and NLR (p < 0.000). Medical nutritional therapy improved these markers, leading to better outcomes. Higher MST scores were linked to longer hospital stays, while proper nutritional management reduced mortality and shortened hospitalization. Conclusion: Early malnutrition screening and appropriate nutritional management in CKD patients improve outcomes by reducing inflammation and mortality, with NLR and albumin serving as key indicators of prognosis.